The forger's identikit: A multi-technique characterization of Pippo Oriani's fake paintings. (November 2022) - Manfriani, C.; Zuena, M.; Ruggiero, L.; Lucarelli, C.; Ridolfi, S.; Tortora, L.; Sodo, A.
Abstract: This work is part of a multi-disciplinary study aimed at creating the first scientific database to support the future authentication of paintings on the art market. In particular, five fake paintings attributed to the Italian painter Pippo Oriani (1909–1972) have been characterized. Since no scientific literature concerning the material composition used by the artist is available, the five paintings were studied with a multi-technique approach aiming at better understanding the forgery process. The obtained results can be used in the future as a first step to support the authentication of Oriani's artworks on the art market. In particular, it allows to evaluate the consistency of data obtained from future scientific investigations on Oriani's artwork with the forgery process reported in the present database. Non-invasive diagnostic tools, such as UV imaging, IR and IR-false colour photography, XRF, μ-Raman and FTIR spectroscopies have been used to fully characterize the fake paintings. The combination of these techniques led to obtaining useful information on the support preparation method, the pictorial materials, and the execution technique of the artist/forger(s). A wide range of inorganic pigments and organic dyes have been detected, together with the use of oil and wax as binders. The results revealed a strong similarity among the different paintings, thus supporting the idea that the forger(s) knew very well the original Oriani's pictorial technique. The detailed identification of all the materials used in the forgery process for Oriani's fake paintings will help to support the authentication of other ambiguous paintings in future cases. Graphical abstract: Image 1 Highlights: Oriani's forger(s) database to support the authentication process has been created. A combined use of imaging and spectroscopic techniques has been adopted. A wide range of inorganic pigments and organic dyes have been identified. Binders include wax and oil, supporting the encaustic technique on cardboard.